TAKRAW SPORT WORLD INNOVATION: HOW TO BE RECOGNIZED THE OLYMPIC GAMES FRONTIER SUPPORTED TAKRAWDIGITAL AND TAKRAWRANKING: A SYSTEMATIC REVIEW - Pavilas, Chaiyasith; Chaiwatcharaporn, Chalerm; Yodmani, Gongsak; Sangnin, Kittikun (Academic Journal of Thailand National Sports University, 2024)
The purpose of systematic review was to investigate Takraw Sport world society, innovations and technology that how to be recognized the Olympic Games frontier in the first time that was supported by the global TakrawDigital, TakrawRanking and Accredit Takraw Ball testing for a new sports event. In Sepaktakraw (ST) games, especially, ST-Summit 2019 updates widely, many countries around the world in which the ST game are enrolled and actively playing organized by ISTAF. These information databases were searched and extracted via indexed publications in SEMA. Scholar, SciELO and SportDiscus. The results showed that the social interaction, innovation and phenomenon involved the evolution and development of the new traditional sport and culture in the events, materials, games and organizations era. The schematic sport events of the World Takraw Sport society consensus and movement of ISTAF which ST-games over 40 years shown as stimulation for a tentative Olympic frontier, nearly. By the main goals of ISTAF, currently, are to spread ST into 75 different countries of four continents and ultimately make it an Olympic Games. Moreover, these innovations may enhance sport participation and standardization of games that support to recognition of the Olympic sports frontier in strategy, leading to the sustainable development of the World Takraw’s society, including others, in future.